Viabilidade técnica da produção de ligante modificado com borracha de pneus inservíveis pelo processo úmido (wet process) através do sistema não estocável (continuous blending), para concreto asfáltico - Dorneles, Fabrício Fagundes (Universidade do Vale do Rio dos Sinos, 2020)
In the last decades, the use of rubber from waste tires in civil construction has been researched, with the objective of giving a correct destination for this waste. The present work had as general objective to carry out an analysis of the technical viability of the production of binder modified with rubber from waste tires by the wet process (Wet Process) through the non-stocking system (Continuous Blending), for asphalt concrete. For the execution of the experiment, the wet process was used, for which different dose formulations of Asphalt-Rubber binder were defined, based on the variation of the main intervening factors in the performance, such as: rubber particle sizes, temperatures and mixing times. To analyze the influence of these variables and also relevant product parameters, the following tests were carried out: Penetration, Softening Point, Thermal Susceptibility Index, Specific Mass and Storage Stability. The results obtained demonstrated as the most important intervening factors, among those analyzed, the percentage of Rubber, followed by the mixing temperature and digestion time. The importance of granulometry was perceived in the fact that the smaller diameter particles have a larger specific surface, facilitating the ligand and modifier interaction, yet it still needs a certain combination between the other variables. It was clear the possibility of the technical feasibility of producing Asphalt-Rubber binder by the wet process (Wet Process) through the non-stockable system (Continuous Blending).
Keywords: Borracha de pneus inservíveis; Ligante modificado; Concreto asfáltico.; Scrap rubber; Modified ligand; Asphalt concrete; ACCNPQ::Engenharias::Engenharia Civil